Prism film formed by compound photocuring adhesive and preparation and application thereof
By using a prism film made of a composite light curing glue composition, the problems of rupture of shape and poor brightness during processing and application of existing prism sheets are solved, and the effects of high abrasion resistance, excellent brightness and high refractive index are achieved.
Patent Information
- Application Number
- CN202411238384.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-03-04
AI Technical Summary
During processing and application, existing prism sheets are prone to problems of shape cracking and poor brightness, and it is difficult to improve their abrasion resistance and optical properties at the same time.
The prism film made of a composite photocuring glue composition is used, and the composition includes 50 wt% to 85 wt% of compound A, 10 wt% to 20 wt% of polyurethane modified acrylate resin, 10 wt% to 20 wt% of epoxy resin, 0.5 wt% to 5 wt% of photoinitiator, 0.1 wt% to 4 wt% of antistatic agent and 0.01 wt% of silicone. The composition has a high refractive index and light dispersion, improving the brightness and abrasion resistance of the prism film.
It realizes high abrasion resistance, excellent brightness and high refractive index of the prism film, while improving adhesion and processability, and is suitable for applications such as backlight modules.
Smart Images

Figure CN119552619A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science and technology, and specifically relates to a prism film composed of a compounded light-curing adhesive and a preparation method and application thereof. Background Art
[0002] Compared with the previous generation of CRT display, LCD has the advantages of small size, low energy consumption, no flicker, low radiation, and pure equality. Since the traditional CRT display screen forms cathode ray tube imaging, it is inevitable that there will be screen flickering caused by scanning frequency limitations and static electricity and radiation caused by electron beam movement. From the display mechanism of LCD, it can be seen that the stable backlight source and the display characteristics of liquid crystal are destined to have a smaller size and lower radiation than CRT, and the picture appears almost at the same time. Not only that, the display power consumption of LCD is mainly concentrated on the backlight source and circuit, which is significantly lower than that of CRT display. However, its disadvantages are also obvious: first, there is a viewing angle, and the viewing range is smaller than CRT; second, there is a response speed, which will produce screen smear; third, the color reproduction and authenticity are not as good as CRT displays; fourth, the brightness is not as good as CRT displays. With major technological breakthroughs again and again, LCD display technology has made great progress in recent decades, the display effect has been continuously improved, and coupled with the control of cost prices, it has successfully become the overlord of the flat panel display industry. However, with the gradual rise and maturity of display technologies led by OLED in recent years and their increasing market share, the dominant position of LCD display technology has been impacted to a certain extent.
[0003] In recent years, various LCD flat panel display technologies and products have developed rapidly. Flat panel display LCD is currently the most widely used flat display technology with the most products. Products have been widely used in various fields, such as LCD and LED LCD display technologies used in televisions, mobile phones, laptops, desktop computer monitors, workstations, industrial monitors, global satellite positioning systems (GPS), personal data processing, game consoles, videophones, portable VCDs, DVDs and other portable devices. Liquid crystal display devices mainly include liquid crystal panels, backlight modules, etc. The backlight module is one of the key components of liquid crystal display devices. Its function is to supply sufficient brightness and uniformly distributed light sources to enable it to display images normally. The backlight module mainly includes a light source, a reflector, a light guide plate, a lower diffusion film, a prism sheet and an upper diffusion film.
[0004] Prism sheet is a film that improves LCD brightness. Because LCD itself does not emit light, it uses a light source (CCFL or LED) to generate light, spreads the light to all areas through a light guide plate, and turns the light source into a surface light source with uniform brightness through a diffuser. In this process, the efficiency of the initial light emitted by the light source gradually decreases. Here, prism sheet is used to convert side light into front light and collect reflected light, thereby increasing brightness. Prism sheet used as a light collecting sheet is an optical sheet with film flexure, in which prisms are arranged in a straight line on one side to form a structured surface, thereby increasing brightness.
[0005] In addition to the physical structure described above, optical materials can be used to improve brightness. An important optical factor in improving brightness is the refractive index. The performance of a prism is proportional to its refractive index.
[0006] Regarding prismatic sheets for improving brightness, optical properties are important influencing factors, including the refractive index of the film and the refractive index of the photocurable material constituting the prismatic sheet. However, the prismatic sheet suffers from prism shape cracking due to the shrinkage of the film and the coating agent, and external forces caused by worker negligence during the transfer or assembly of the backlight module after processing. Photocurable monomers and compositions applied to conventional prismatic sheets cannot solve this problem. In addition, as a solution to this problem, a prismatic sheet using a photocurable composition with self-recovery properties has been proposed. Polyurethane acrylate with low refractive index and excellent elasticity is used to provide self-recovery, but it cannot help improve brightness.
[0007] The inventors surprisingly found that the UV curable adhesive composition of the present invention has high scratch resistance, excellent brightness, high refractive index and good adhesion. Summary of the invention
[0008] In one aspect, a photocurable adhesive composition for a prism layer is provided, wherein the composition comprises the following components in parts by mass:
[0009] Compound A as shown in formula (I): 50wt%-85wt%;
[0010] Polyurethane modified acrylate resin: 10wt%-20wt%;
[0011] Epoxy resin: 10wt%-20wt%;
[0012] Photoinitiator: 0.5wt%-5wt%;
[0013] Antistatic agent: 0.1wt%-4wt%;
[0014] Silicone: 0.01wt%-1wt%.
[0015]
[0016] wherein R is independently selected from H, alkyl, alkoxy or aryl;
[0017] X is selected from
[0018] Wherein R1 is independently selected from H, alkyl, alkoxy;
[0019] The alkyl group is selected from: a C1-20 straight chain or branched chain alkyl group;
[0020] The aryl group is selected from: C6-C20 aryl group;
[0021] The alkoxy group is selected from: C1-20 alkoxy group.
[0022] Furthermore, the alkyl group is selected from a C1-6 straight chain or branched alkyl group; the C6-C20 aryl group is selected from a phenyl group; and the alkoxy group is selected from a C1-6 alkoxy group.
[0023] Further, R is selected from H, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl; R1 is independently selected from H, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, phenyl, naphthyl, anthracenyl, methoxy, ethoxy, and propoxy.
[0024] Furthermore, the UV curable adhesive composition has a refractive index greater than 1.48 and a light dispersion greater than 45 measured by Abbe number.
[0025] Furthermore, the UV curable adhesive composition has a refractive index greater than 1.49 and a light dispersion greater than 53 measured by Abbe number.
[0026] Furthermore, the polyurethane modified acrylate resin is prepared by the following method:
[0027] (1) Add diisocyanate to a reaction flask, raise the temperature to 50-70° C., dropwise add diol, react, and cool to obtain product 1;
[0028] (2) Adding the acrylic acid ester monomer to a reaction bottle under light-proof conditions, heating, slowly adding ethanolamine dropwise, reacting, and cooling to obtain product 2;
[0029] (3) Under argon protection and light-proof conditions, product 2 is added to a reaction flask, the temperature is raised to 50-70° C., product 1 is added dropwise, the reaction is carried out, and the temperature is lowered to obtain the polyurethane-modified acrylate resin.
[0030] Further, the epoxy resin includes a bisphenol A epoxy resin having a high Tg value and a bisphenol A epoxy resin having a low Tg value.
[0031] Furthermore, it is characterized in that the bisphenol A epoxy resin with a high Tg value is any one or more of Nan Ya NPES-901, NPES-901H, NPES-902, NPES-902H, NPES-903K, NPES-903 and NPES-903H, and the bisphenol A epoxy resin with a low Tg value can be any one or more of EDR-331, DER-332 and DER-383.
[0032] Furthermore, the diisocyanate is selected from any one or more combinations of toluene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, dimethylbiphenyl diisocyanate, and diphenylmethane diisocyanate.
[0033] Furthermore, the diol is an alkoxy ether having a number average molecular weight of 500 to 2500; preferably, the diol is polyethylene glycol and / or polypropylene glycol; further preferably, the diol is polypropylene glycol-1000 and / or polypropylene glycol-2000.
[0034] Further, the antistatic agent may be an antistatic agent commonly used in the prior art, the antistatic agent may be prepared by combining a conventional reactive silicone resin and an ion conductive polymer, wherein ethylene oxide or propylene oxide is ionically combined with an ion conductive metal, or the antistatic agent may be obtained from a commercially available product. For example, at least one selected from the group consisting of HR-E, ELECON-600DA, ELECON-700DA (all available from NanoChemTech), and an ionic liquid series including IL-A21-9, IL-A2, and IL-A5 (all available from KOEI) may be used.
[0035] In terms of the solid content in the photocurable resin composition, the content of the antistatic agent may be 0.1wt% to 8wt%. Within the above range, an antistatic effect can be exhibited, and in a high temperature / high humidity environment, each ion component will not float on the surface in large quantities, thereby not causing the interface adhesion, mechanical properties and optical properties of the prism to deteriorate. Specifically, the content of the antistatic agent may be 0.1wt% to 4wt%.
[0036] Furthermore, the silicone additive can be an organic modified silicone, such as a hydroxyl-containing organic modified silicone, an amino-containing organic modified silicone, a carboxyl-containing organic modified silicone, etc., and can be specifically selected from BYK-3700, BYK-370, BYK-375, BYK-377, X-22-4015, X-22-4952, X-22-4272, KF-8004, KF-8002, X-22-3701E, etc.
[0037] The content of the silicone additive may be 0.01 wt%-3w%, preferably 0.01 wt%-1w%.
[0038] Further, the photoinitiator may be a sulfonium salt cationic photoinitiator, specifically Omnicat 550 and Omnicat 432. The content of the initiator may be 0.5 wt % to 7 wt %. Within the above range, due to the high photoreactivity, the mechanical strength of the prism will not be reduced, and the optical properties of the prism layer will not deteriorate, that is, the prism layer will not turn yellow. Specifically, the content of the initiator may be 0.5 wt % to 5 wt %.
[0039] In another aspect of the present invention, the present invention provides a prism film, which comprises a prism layer and a transparent substrate from top to bottom; the prism layer is prepared from the photocurable adhesive composition.
[0040] Furthermore, the transparent substrate is selected from: glass, PET or PC.
[0041] Beneficial Effects
[0042] Compared with the prior art, the photocurable adhesive composition prepared according to the present invention has high scratch resistance, excellent brightness, high refractive index and adhesion by compounding the raw materials of the photocurable adhesive composition. The curable adhesive composition of the present invention contains compound A, polyurethane modified acrylate resin and epoxy resin, wherein the polyurethane modified acrylate resin improves fluidity and exhibits high adhesion, improves wear resistance and flexibility; compound A has a high refractive index, and since no halogen is introduced into the compound, it maintains a high refractive index while also having low dispersion; the use of epoxy resin allows the composition to adjust the hardness of the photocurable adhesive composition during application, so that it can be better used at room temperature and more closely fit the surface of the substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 , Microscopic image of prism film
[0044] Figure 2 , Brightness enhancement principle diagram of BEF prism film DETAILED DESCRIPTION
[0045] Next, the structure and function of the present invention will be explained in more detail with reference to the following examples. These examples are provided for illustrative purposes only and are not to be construed in any way as limiting the present invention.
[0046] The details of the components used in the examples and comparative examples are as follows:
[0047] The epoxy resins are Nan Ya NPES-902 and EDR-331.
[0048] HR-E, a silicone-modified ion-conductive acrylate obtained from NanoChemTech, was used as an antistatic agent.
[0049] UV-3700 obtained from BYK was used as a silicone additive.
[0050] Omnicat 550 was used as initiator.
[0051] Preparation Example 1:
[0052] Preparation of compound A1: Place a 250mL four-necked flask in a pre-built ice-water bath, and introduce nitrogen to replace the air in the flask. Weigh a certain amount of 4,4-dimercaptodiphenyl sulfide and methacryloyl chloride in proportion, with a molar ratio of 1:4, 1% of the reactant mass of catalyst tetrabutylammonium bromide (TBAB), and an appropriate amount of inhibitor hydroquinone. Add 4,4-dimercaptodiphenyl sulfide and catalyst tetrabutylammonium bromide to a four-necked flask, dissolve with an appropriate amount of dichloromethane, dissolve methacryloyl chloride with an appropriate amount of dichloromethane, and prepare acid-binding agent potassium hydroxide for use. Add methacryloyl chloride to the four-necked flask and drop the acid-binding agent, stirring while dropping, dripping for about 30 minutes, and then continue to react for 2-3 hours. The organic layer was separated after standing for stratification, and washed once with 10% hydrochloric acid, 10% sodium bicarbonate solution and sodium chloride solution respectively, and then washed with water until neutral, and then dried with a desiccant and distilled under reduced pressure to obtain a colorless oily product, which was recrystallized with petroleum ether to obtain needle-shaped crystals.
[0053] The structure of compound A1 is:
[0054]
[0055] Preparation Example 2
[0056] Preparation of compound A2: Place a 250mL four-necked flask in a pre-built ice-water bath, and introduce nitrogen to replace the air in the flask. Weigh a certain amount of 2,5-dimercaptothiadiazole and methacryloyl chloride in proportion, with a molar ratio of 1:4, 1% of the reactant mass of catalyst tetrabutylammonium bromide (TBAB), and an appropriate amount of inhibitor hydroquinone. Add 2,5-dimercaptothiadiazole and catalyst tetrabutylammonium bromide to a four-necked flask, dissolve with an appropriate amount of acetone, dissolve methacryloyl chloride in an appropriate amount of acetone for standby use, and prepare acid-binding agent potassium hydroxide for standby use. Add methacryloyl chloride to the four-necked flask and drop the acid-binding agent, stirring while dropping, dripping for about 30 minutes, and then continue to react for 2-3 hours. The organic layer was separated after standing for stratification, and washed once with 10% hydrochloric acid, 10% sodium bicarbonate solution and sodium chloride solution respectively, and then washed with water until neutral, and then dried with a desiccant and distilled under reduced pressure to obtain a colorless oily product, which was recrystallized with petroleum ether to obtain needle-shaped crystals.
[0057] The structure of compound A2 is:
[0058]
[0059] Preparation Example 3:
[0060] Preparation of compound A3: Place a 250mL four-necked flask in a pre-built ice-water bath, and introduce nitrogen to replace the air in the bottle. Weigh a certain amount of 4,4-dihydroxydiphenyl ether and methacryloyl chloride in proportion, with a molar ratio of 1:4, 1% of the reactant mass of catalyst tetrabutylammonium bromide (TBAB), and an appropriate amount of inhibitor hydroquinone. Add 4,4-dihydroxydiphenyl ether and catalyst tetrabutylammonium bromide to a four-necked flask, dissolve with an appropriate amount of dichloromethane, dissolve methacryloyl chloride with an appropriate amount of dichloromethane, and prepare acid-binding agent potassium hydroxide for use. Add methacryloyl chloride to the four-necked flask and drop the acid-binding agent, stirring while dropping, dripping for about 30 minutes, and then continue to react for 2-3 hours. The organic layer was separated after standing for stratification, and washed once with 10% hydrochloric acid, 10% sodium bicarbonate solution and sodium chloride solution respectively, and then washed with water until neutral, and then dried with a desiccant and distilled under reduced pressure to obtain a colorless oily product, which was recrystallized with petroleum ether to obtain needle-shaped crystals.
[0061] The structure of compound A3 is:
[0062]
[0063] Preparation Example 4:
[0064] Preparation of compound A4: Place a 250mL four-necked flask in a pre-built ice-water bath, and introduce nitrogen to replace the air in the flask. Weigh a certain amount of 4,4-dihydroxydiphenyl sulfide and methacryloyl chloride in proportion, with a molar ratio of 1:4, 1% of the reactant mass of catalyst tetrabutylammonium bromide (TBAB), and an appropriate amount of inhibitor hydroquinone. Add 4,4-dihydroxydiphenyl ether and catalyst tetrabutylammonium bromide to a four-necked flask, dissolve with an appropriate amount of dichloromethane, dissolve methacryloyl chloride with an appropriate amount of dichloromethane, and prepare acid-binding agent potassium hydroxide for use. Add methacryloyl chloride to the four-necked flask and drop the acid-binding agent, stirring while dropping, dripping for about 30 minutes, and then continue to react for 2-3 hours. The organic layer was separated after standing for stratification, and washed once with 10% hydrochloric acid, 10% sodium bicarbonate solution and sodium chloride solution respectively, and then washed with water until neutral, and then dried with a desiccant and distilled under reduced pressure to obtain a colorless oily product, which was recrystallized with petroleum ether to obtain needle-shaped crystals.
[0065] The structure of compound A4 is:
[0066]
[0067] Preparation Example 5
[0068] Preparation of polyurethane modified acrylate:
[0069] (1) Under argon protection, 348.3 g of toluene diisocyanate was added to a reaction flask, the temperature was raised to 60-65° C., and 1000 g of diol polypropylene glycol-1000 was added dropwise. After the addition was completed, the reaction was continued at the temperature for 4.5 h, the reaction was stopped, and the temperature was lowered to obtain product 1;
[0070] (2) Under light-proof conditions, 600.7 g of tripropylene glycol diacrylate was added to a reaction bottle, the temperature was raised to 50° C., stirred, and then 61 g of ethanolamine was slowly added dropwise. After the addition was complete, the reaction was continued at this temperature for 2 days. After the chromatographic detection showed no peak of the raw material, the reaction was stopped and the temperature was lowered to obtain product 2;
[0071] (3) Under argon protection and light-proof conditions, 661.7 g of product 2 was added to a reaction flask, the temperature was raised to 60-65° C., stirred, and 674.1 g of product 1 was added dropwise. After the addition was completed, the reaction was continued at the temperature for 4-5 h. When no -NCO group was found, the reaction was stopped and the temperature was lowered to obtain the polyurethane-modified acrylate resin, which was recorded as UV1.
[0072] Example 1-2 and Comparative Example 1-2: Preparation of Photocurable Adhesive Composition
[0073] The components were mixed according to the composition listed in Table 1 (as shown below) to prepare a photocurable resin composition.
[0074] Table 1
[0075]
[0076] Performance evaluation: The compositions of Examples 1-2 and Comparative Examples 1-2 were prepared into films.
[0077] Each photocurable adhesive composition produced in Examples 1-2 and Comparative Examples 1-2 is coated on a soft mold or a metal mold engraved with a prismatic layer. When the coating of the composition on the base film and the engraved mold is in contact on one side, the coated composition is photocured by ultraviolet radiation. The coating bonded to the base film and cured is separated from the engraved mold to produce a prismatic film having a prismatic layer formed on one side of the base film. At this time, the prismatic layer is formed to a height of 30 μm, and ultraviolet rays with a wavelength of 190 nm are used with an electrodeless ultraviolet radiation device (600 W / inch) equipped with a D-type bulb at a rate of 500 mJ / cm 2 radiation.
[0078] The following properties were evaluated for each photocurable resin composition and each prism film, and the results are shown in Table 2 (see the table below).
[0079] <Evaluation Method>
[0080] 1. Refractive index
[0081] A refractometer (Model: 1T, ATAGOABBE, Japan) was used to measure the refractive index of each photocurable resin composition. For the measurement, a D-line sodium lamp having a wavelength of 589.3 nm was used as a light source.
[0082] 2. Brightness (Cd / m 2 )
[0083] Each prism film was fixed on a backlight unit of a 17-inch liquid crystal display, and then the brightness was measured at 25 points and 9 points on the liquid crystal display with a brightness photometer (model: BM-7, Topcon, Japan) to calculate an average value.
[0084] 3. Scratch resistance (g)
[0085] Each composition was coated on a transparent PET base film and cured, and then the cured prismatic layer was turned over to contact the opposite glass surface. A balance weight of up to 500 g was placed thereon and moved back and forth 10 times within a distance of 10 cm, and then the weight of the balance weight was measured at the point where the prism began to be damaged.
[0086] 4. Yellowing (ΔYI)
[0087] Each prism film was heated at 50°C and 0.34 W / m 2 The samples were placed in a Weather-O-meter for 200 hours and then the fading degree was measured with a colorimeter.
[0088] 5. Adhesion (number of matrices remaining / 100)
[0089] Each photocurable resin composition was coated on a transparent PET base film and cured, and then only the cured prismatic layer was cut into pieces having a size of 10 mm. 2 Then, tape was attached to it and peeled off strongly in the vertical direction, and then the separated matrices were counted.
[0090] 6. Surface resistance (Ω / cm 2 )
[0091] Each photocurable resin composition was applied to a transparent PET base film and cured, and then voltage was applied and surface resistance was measured using DSM-8103 (Toa Corporation, Japan).
[0092] 7. Release properties
[0093] Each photocurable resin composition was placed between a metal mold engraved with a prism shape and a polyester base film to form a laminate, and then the base film was peeled from the metal mold. The workability, such as releasing sound, was expressed in the range of 0 to 10. Here, 10 was defined as excellent release performance.
[0094] Table 2
[0095]
[0096] As shown in Table 2, the prism films formed from the photocurable resin compositions according to Examples 1 to 2 have high scratch resistance, improved brightness and refractive index, and increased adhesion to the base film. In addition, these prism films have a viscosity suitable for processing, thereby exhibiting good demolding properties. In addition, the prism film composition contains an antistatic agent, thereby having an antistatic effect.
[0097] Although some embodiments have been disclosed herein, it should be understood that these embodiments are provided by way of illustration only and that various modifications, changes and substitutions may be made without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention shall be limited only by the appended claims and their equivalents.
Claims
1. A photocurable adhesive composition for a prism layer, characterized in that: The composition comprises the following components by mass: Compound A as shown in formula (I): 50wt%-85wt%; Polyurethane modified acrylate resin: 10wt%-20wt%; Epoxy resin: 10wt%-20wt%; Photoinitiator: 0.5wt%-5wt%; Antistatic agent: 0.1wt%-4wt%; Silicone: 0.01wt%-1wt%. Formula (I) Wherein, R is independently selected from H, alkyl, alkoxy, aryl; X is selected from Wherein R1 is independently selected from H, alkyl, alkoxy; The alkyl group is selected from: a C1-20 straight chain or branched chain alkyl group; The aryl group is selected from: C6-C20 aryl group; The alkoxy group is selected from: C1-20 alkoxy group.
2. The composition according to claim 1, characterized in that The alkyl group is selected from a C1-6 straight chain or branched alkyl group; the C6-C20 aryl group is selected from a phenyl group; and the alkoxy group is selected from a C1-6 alkoxy group.
3. The composition according to any one of claims 1 to 2, characterized in that R is selected from H, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl; R1 is independently selected from H, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, phenyl, naphthyl, anthracenyl, methoxy, ethoxy, and propoxy.
4. The composition according to claim 1, characterized in that The UV curable adhesive composition has a refractive index greater than 1.48 and a light dispersion greater than 45 measured by an Abbe number.
5. The composition according to claim 4, characterized in that The UV curable adhesive composition has a refractive index greater than 1.49 and a light dispersion greater than 53 measured by an Abbe number.
6. The composition according to claim 1, characterized in that The polyurethane modified acrylate resin is prepared by the following method: (1) Add diisocyanate to a reaction flask, raise the temperature to 50-70° C., dropwise add diol, react, and cool to obtain product 1; (2) Adding the acrylic acid ester monomer to a reaction bottle under light-proof conditions, heating, slowly adding ethanolamine dropwise, reacting, and cooling to obtain product 2; (3) Under argon protection and light-proof conditions, product 2 is added to a reaction flask, the temperature is raised to 50-70° C., product 1 is added dropwise, the reaction is carried out, and the temperature is lowered to obtain the polyurethane-modified acrylate resin.
7. The composition according to claim 6, characterized in that The epoxy resin includes a bisphenol A epoxy resin having a high Tg value and a bisphenol A epoxy resin having a low Tg value.
8. The composition according to claim 7, characterized in that The bisphenol A epoxy resin with a high Tg value can be any one or more of Nan Ya NPES-901, NPES-901H, NPES-902, NPES-902H, NPES-903K, NPES-903 and NPES-903H, and the bisphenol A epoxy resin with a low Tg value can be any one or more of EDR-331, DER-332 and DER-383.
9. The composition according to claim 6, characterized in that The diisocyanate is selected from any one or more combinations of toluene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, dimethylbiphenyl diisocyanate, and diphenylmethane diisocyanate; the diol is selected from polyethylene glycol and / or polypropylene glycol.
10. The composition according to claim 1, characterized in that The antistatic agent is selected from HR-E, ELECON-600DA, ELECON-700DA, IL-A21-9, IL-A2, and IL-A5; the silicone additive is selected from BYK-3700, BYK-370, BYK-375, BYK-377, X-22-4015, X-22-4952, X-22-4272, KF-8004, KF-8002, and X-22-3701E; and the photoinitiator is selected from Omnicat550 and Omnicat432.
11. A prismatic film, characterized in that: The prism film comprises a prism layer and a transparent substrate from top to bottom; the prism layer is prepared by the curing adhesive according to any one of claims 1 to 10.
Citation Information
Patent Citations
High refractive index, durable hard coats
CN101095065A
Photocurable adhesive, preparation method and application thereof
CN112126402A
Photo-thermal dual-curing resin composition as well as preparation method and application thereof
CN113652186A